SPECIFIC CHARACTERISTICS OF DOUBLE FERTILITY SIMMENTAL CATTLE (COWS) IMPORTED TO KARAKALPAKSTAN (Web of Teachers: Inderscience Research, 2024)
The article provides information about the natural economic situation of the "Konyratbay Mehri" livestock farm, where experiments and methods of effective use of Simmental cattle brought to Karakalpakstan from Germany are carried out.